Job and worker turnover in German establishments - Bellmann, Lutz; Gerner, Hans-Dieter; Upward, Richard (Wiley, 2018)
We use a simple non-parametric regression approach to measure the relationship between employment growth, hirings and separations in a large panel of German establishments over the period 1993--2014. Although it is often claimed that firms in Europe have less flexibility in their ability to hire and fire, we find that the relationship between employment growth and worker flows in German establishments is very similar to the behaviour of US establishments. The relationship is stable over time, even during the 2008-09 economic crisis, and across different types of establishment. We verify our results with independent measures from administrative data. We suggest that this result is due to: the strong relationship between employment reductions and voluntary separations; the low level of "churning"; and the heterogeneity of jobs within establishments.